GnRH Agonist Trigger and LH Activity Luteal Phase Support versus hCG Trigger and Conventional Luteal Phase Support in Fresh Embryo Transfer IVF/ICSI Cycles—A Systematic PRISMA Review and Meta-analysis - Haahr, Thor; Roque, Matheus; Esteves, Sandro C.; Humaidan, Peter (Frontiers in Endocrinology, 2017)
Introduction The use of GnRH agonist (GnRHa) for final oocyte maturation trigger in oocyte donation and elective frozen embryo transfer cycles is well established due to lower ovarian hyperstimulation syndrome (OHSS) rates as compared to hCG trigger. A recent Cochrane meta-analysis concluded that GnRHa trigger was associated with reduced live birth rates (LBRs) in fresh autologous IVF cycles compared to hCG trigger. However, the evidence is not unequivocal, and recent trials have found encouraging reproductive outcomes among couples undergoing GnRHa trigger and individualized luteal LH activity support. Thus, the aim was to compare GnRHa trigger followed by luteal LH activity support with hCG trigger in IVF patients undergoing fresh embryo transfer. Material and methods We conducted a systematic review and meta-analysis of randomized trials published until December 14, 2016. The population was infertile patients submitted to IVF/ICSI cycles with GnRH antagonist cotreatment who underwent fresh embryo transfer. The intervention was GnRHa trigger followed by LH activity luteal phase support (LPS). The comparator was hCG trigger followed by a standard LPS. The critical outcome measures were LBR and OHSS rate. The secondary outcome measures were number of oocytes retrieved, clinical and ongoing pregnancy rates, and miscarriage rates. Results A total of five studies met the selection criteria comprising a total of 859 patients. The LBR was not significantly different between the GnRHa and hCG trigger groups (OR 0.84, 95% CI 0.62, 1.14). OHSS was reported in a total of 4/413 cases in the GnRHa group compared to 7/413 in the hCG group (OR 0.48, 95% CI 0.15, 1.60). We observed a slight, but non-significant increase in miscarriage rate in the GnRHa triggered group compared to the hCG group (OR 1.85; 95% CI 0.97, 3.54). Conclusion GnRHa trigger with LH activity LPS resulted in comparable LBRs compared to hCG trigger. The most recent trials reported LBRs close to unity indicating that individualization of the LH activity LPS improved the luteal phase deficiency reported in the first GnRHa trigger studies. However, LPS optimization is needed to further limit OHSS in the subgroup of normoresponder patients (<14 follicles ≥ 11 mm). Prospero registration number CRD42016051091